3x2+13x-10 = (3x-2)(x+5) when factored
6x2+13x-5 = (2x+5)(3x-1) when factored
(3x - 4)(7x + 5)
3x + 10x - 48 = 0 13x = 48 x = 3.692307692
The expression 10x + 7 + 3x can be simplified by combining like terms. Like terms are terms that have the same variable raised to the same power. In this case, the like terms are 10x and 3x, as they both have the variable x raised to the power of 1. Combining these like terms gives us 13x. Therefore, the simplified expression is 13x + 7.
3x2+13x-10 = (3x-2)(x+5) when factored
(3x + 2)(2x + 3)
(5x - 4)(3x + 5)
13x+27=3x+32 Reorder 13x-3x=32-27 Simplify 10x=5 Simplify x=5/10 Simplify x=1/2 Answer
(5x - 4)(3x + 5)
Well, well, well, looks like someone needs a math lesson! 10x plus 3x equals 13x. It's as simple as that, honey. Math doesn't have to be a headache if you just pay attention.
3x + 12 + 10x = 13x + 12
3x plus 10x - 7With out knowing what ' x ' actually is.. it will reduce down to.3x + 10 x - 7=13x - 7
13x + 7
3x-13x+4=0 -10x+4=0 4=10x 4/10=x simplified: x= 2/5
6x2+13x-5 = (2x+5)(3x-1) when factored
5x2 + 3x + 8x2 = 13x2 + 3x = x(13x + 3)